Targeting Hypoxia-Inducible Factor-1α in Pancreatic Cancer: siRNA Delivery Using Hyaluronic Acid-Displaying Nanoparticles - Alice Spadea; Annalisa Tirella; Julio Manuel Rios de la Rosa; Enrique Lallana; Manal Mehibel; Brian Telfer; Nicola Tirelli; Margaret Jayne Lawrence; Kaye J. Williams; Ian J. Stratford; Marianne Ashford (MDPI AG, 2024)
Background/Objectives: Conventional anticancer therapies often lack specificity, targeting both cancerous and normal cells, which reduces efficacy and leads to undesired off-target effects. An additional challenge is the presence of hypoxic regions in tumors, where the Hypoxia Inducible Factor (HIF) transcriptional system drives the expression of pro-survival and drug resistance genes, leading to radio- and chemo-resistance. This study aims to explore the efficacy of targeted nanoparticle (NP)-based small interfering RNA (siRNA) therapies in downregulating these genes to enhance treatment outcomes in pancreatic cancer, a tumor type characterized by high CD44 expression and hypoxia. Methods: We utilized hyaluronic acid (HA)-displaying nanoparticles composed of positively charged chitosan (CS) complexed with siRNA to target and knock down HIF-1α in pancreatic cancer cells. Two NP formulations were prepared using either low molecular weight (LMW) or high molecular weight (HMW) CS. These formulations were evaluated for their internalization by cells and their effectiveness in gene silencing, both in vitro and in vivo. Results: The study found that the molecular weight (MW) of CS influenced the interaction between HA and CD44, as well as the release of siRNA upon internalization. The LMW CS formulation shows faster uptake kinetics, while HMW CS is more effective in gene knockdown across different cell lines in vitro. In vivo, both were able to significantly knockdown HIF-1α and some of its downstream genes. Conclusions: The results suggest that HMW and LMW CS-based NPs exhibit distinct characteristics, showing that both MWs have potential for targeted pancreatic cancer therapy by influencing different aspects of delivery and gene silencing, particularly in the hypoxic tumor microenvironment.